e-Business and Telecommunications 7th International Joint Conference, ICETE 2010, Athens, Greece, July 26-28, 2010, Revised Selected Papers - Obaidat, Mohammad S.; Tsihrintzis, George A.; Filipe, Joaquim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Joint Conference on e-Business and Telecommunications, ICETE 2010, held in Athens, Greece, in July 2010. The 28 revised full papers presented together with 1 invited paper in this volume were carefully reviewed and selected from 422 initial submissions. They have passed two rounds of selection and improvement. According to the topics of the particular conference the papers are organized in thematical parts on data communication networking (DCNET), e-business (ICE-B), optical communication systems (OPTICS), security and cryptography (SECRYPT), signal processing and multimedia applications (SIGMAP), wireless information networks and systems (WINSYS).
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Coding theory; Computer software; Multimedia systems; Computer Science; Computer Communication Networks; e-Commerce/e-business.; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Multimedia Information Systems; Algorithm Analysis and Problem Complexity